Controllable synthesis of nonlayered high-κ Mn3O4 single-crystal thin films for 2D electronics - Jiashuai Yuan; Chuanyong Jian; Zhihui Shang; Yu Yao; Bicheng Wang; Yixiang Li; Rutao Wang; Zhipeng Fu; Meng Li; Wenting Hong; Xu He; Qian Cai; et al. (Nature Communications)
Abstract Two-dimensional (2D) materials have been identified as promising candidates for future electronic devices. However, high dielectric constant (κ) materials, which can be integrated with 2D semiconductors, are still rare. Here, we report a hydrate-assisted thinning chemical vapor deposition (CVD) technique to grow manganese oxide (Mn3O4) single crystal nanosheets, enabled by a strategy to minimize the substrate lattice mismatch and control the growth kinetics. The material demonstrated a dielectric constant up to 135, an equivalent oxide thickness (EOT) as low as 0.8 nm, and a breakdown field strength (E bd) exceeding 10 MV/cm. MoS2 field-effect transistors (FETs) integrated with Mn3O4 thin films through mechanical stacking method operate under low voltages (<1 V), achieving a near 108 Ion/Ioff ratio and a subthreshold swing (SS) as low as 84 mV/dec. The MoS2 FET exhibit nearly zero hysteresis (<2 mV/MV cm⁻¹) and a low drain-induced barrier lowering (~20 mV/V). This work further expands the family of 2D high-κ dielectric materials and provides a feasible exploration for the epitaxial growth of single-crystal thin films of non-layered materials.